Assessing the visibility of raised pavement markers and alternative forms of delineation - Bullough, John D.; Liu, Xiang (Transport, 2020)
Raised Pavement Markers (RPMs) are used by a number of transportation agencies with the objective of improving roadway safety, especially in complex roadway geometries and along wet roads. Because of maintenance and cost issues, many transportation agencies are exploring alternatives to RPMs such as wet reflective pavement tape and barrier-mounted reflective delineators. In order to assess the relative potential of these devices to contribute to nighttime driving safety, the luminances of new and used RPM samples from different manufacturers and having different colors and of several alternative delineation devices were measured in the laboratory using a range of geometric conditions relevant to the driving task. From these data, Luminances under representative low-beam headlight illumination were determined and these quantities were used to estimate driver visual performance. Large variations in luminance yielded relatively small differences in visual performance for a viewing distance of 100 m, primarily because of the plateau characteristic of visual performance. Differences in threshold visibility distances were greater, with distances at identification threshold for the devices measured ranging approximately from 150 to 400 m. Used RPMs had luminances 20…30% lower than new RPMs but similar visibility characteristics as new devices. The analysis method in this study may be useful for practitioners seeking to characterize the visual effectiveness of RPMs and other roadway delineation devices and systems.